Way to go - "Chatterjee,Upamanyu" (New Delhi, 2010)
For not having loved one$1 (Bs dead father enough, could one make amends by loving one$1 (Bs child more? In powerful, austere prose shot through with black humour, Upamanyu Chatterjee has produced an intensely moving examination of family ties and the redemptive power of love, however imperfect, in the midst of death and degeneration.s
Keywords: English Fiction